ANALISIS VARIASI BAHASA DALAM BENTUK ALIH KODE PADA MAHASISWA PRODI PENDIDIKAN BAHASA INDONESIA, UNIVERSITAS DHARMAS INDONESIA - Faradilla Intan Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research is motivated by the language transition that occurs in both formal and informal situations. In this research, the focus of the study is code switching on FKIP UNDHARI students of Indonesian Language Study Program. This study aims to describe the code switching in FKIP students of the Indonesian Dharmas University (UNDHARI) Indonesian Language Education Study Program in communication outside the classroom and to describe the factors that influence code switching in communication outside the classroom. This study uses qualitative methods which are descriptive research and tend to use analysis. The data obtained in this study were obtained from student speech that occurred in the form of code switching in communication, both in formal and informal situations. The technique in collecting data in this study is to use observation, interview, and note-taking techniques. The subjects in this study were students of Indonesian language education courses, faculty of education and education, dharmas university of Indonesia. The results showed that: (1) the form of code switching for Indonesian Language Study Program students. the factors causing code switching for students who speak Minang, because speakers deliberately switch to Indonesian so that the intimacy between the speaker and the interlocutor is more established. The transition is done by speakers consciously. The occurrence of code switching in the conversation is caused by the speaker fator and the interlocutor. Listeners or opponents said opponents. The code switching is included in the type of internal code switching (2) the form of code transfer The presence of a third person. the presence of a third person or another person who does not have the same language background as the language being spoken by the speaker and the interlocutor causes code switching. The presence of a third person determines the language changes and variants that will be used.